2023
DOI: 10.3389/fsoc.2023.1281912
|View full text |Cite
|
Sign up to set email alerts
|

Distress in the care of people with chronic low back pain: insights from an ethnographic study

Miriam Dillon,
Rebecca E. Olson,
Stefanie Plage
et al.

Abstract: IntroductionDistress is part of the experiences and care for people with chronic low back pain. However, distress is often pathologised and individualised; it is seen as a problem within the individual in pain and something to be downplayed, avoided, or fixed. To that end, we situate distress as a normal everyday relational experience circulating, affecting, moving in, through, and across bodies. Challenging practices that may amplify distress, we draw on the theorisation of affect as a relational assemblage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…This lack of awareness among physiotherapists might be related to the misconception of mental health spectrum which extends beyond just the realm of mental disorders, as highlighted in the exchange between McGrath et al 19 and Heywood et al 20 Where McGrath et al, sheds light on the intersection between physical therapy and mental well-being, emphasizing that mental health encompasses a broader spectrum of factors beyond diagnosable mental disorders, including emotional well-being, resilience, and overall psychological functioning. Dillon et al 21 revealed the multifaceted nature of mental health and the influence of psychosocial factors, such as distress and coping mechanisms, on individuals’ experiences of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of awareness among physiotherapists might be related to the misconception of mental health spectrum which extends beyond just the realm of mental disorders, as highlighted in the exchange between McGrath et al 19 and Heywood et al 20 Where McGrath et al, sheds light on the intersection between physical therapy and mental well-being, emphasizing that mental health encompasses a broader spectrum of factors beyond diagnosable mental disorders, including emotional well-being, resilience, and overall psychological functioning. Dillon et al 21 revealed the multifaceted nature of mental health and the influence of psychosocial factors, such as distress and coping mechanisms, on individuals’ experiences of chronic pain.…”
Section: Discussionmentioning
confidence: 99%